PENGARUH KUALITAS PELAYANAN DAN KUALITAS PEMBELAJARAN DARING TERHADAP KEPUASAN MAHASISWA DIMASA PANDEMI COVID-19 - Siti Rokhani; Peggy Ratna Marlianingrum (Journal of Management Small and Medium Enterprises (SMEs), 2021)
The Covid-19 pandemic is a new challenge for the world of education, currently higher education institutions (PT) are required to develop creativity and innovation in the use of technology in order to ensure that the learning process can still be conveyed properly. We can see and feel the continuity of the world of education in the future from this pandemic situation, with the help of technology, we can carry out the learning process anywhere and anytime. Higher education has an important responsibility in order to produce human resources who are able to compete in an all-digital industrial era. This makes universities continue to make improvements in terms of service quality, quality of learning, and quality of graduates in order to create a positive image of the college which will have an impact on student satisfaction and increase the productivity of consumer interest in higher education. This research is a quantitative research. The purpose of this study was to determine whether the quality of service and quality of online learning had an effect on student satisfaction during the Covid-19 pandemic, and it is hoped that from this study, it could provide information on online learning methods that were effectively used during this pandemic in improving higher education management Based on this, research has been carried out on 200 samples of respondents (active students) who were used to provide information by distributing questionnaires that were processed with data analysis of validity tests, reliability tests, Average Variance Extracted (AVE), and R square analysis. Based on the results of the analysis and discussion, it can be concluded that service quality has a positive and significant effect on student satisfaction, likewise the quality of online learning also has a positive and significant effect on student satisfaction. Improving the quality of learning with face-to-face learning provides more student satisfaction, to facilitate the absorption of courses. Keywords: Service Quality, Online Learning, Satisfaction, Students